2020
DOI: 10.1136/bmjopen-2020-039189
|View full text |Cite
|
Sign up to set email alerts
|

Why some women who attend focused antenatal care fail to deliver in health facilities: a qualitative study of women’s perspectives from slums of Addis Ababa, Ethiopia

Abstract: ObjectiveThe purpose of this study was to explore why some women who attend focused antenatal care (FANC) fail to deliver in health facilities from slums of Addis Ababa, Ethiopia.SettingPublic health facilities (three health centres and one district hospital).Study designA qualitative exploratory and descriptive research design was used.Study participantsStudy participants comprised women of reproductive age (18–49 years) living in slum areas of Addis Ababa, Ethiopia. We used 20 in-depth audio-recorded intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
3
8
0
Order By: Relevance
“…Therefore, women recommend that more delivery beds (couches), medicines, and medical facilities, such as ultrasound exams, should be made available. The results of the research are consistent with prior studies [ 6 , 9 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Therefore, women recommend that more delivery beds (couches), medicines, and medical facilities, such as ultrasound exams, should be made available. The results of the research are consistent with prior studies [ 6 , 9 ].…”
Section: Discussionsupporting
confidence: 92%
“…A similar study in Lagos, Nigeria [ 31 ], and Addis Ababa Slums in Ethiopia [ 6 ] showed a financial barrier to women living in urban poor populations using health facilities for delivery care. Policymakers and government authorities should take note of our findings to provide skilled delivery care in neglected metropolitan areas.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations